Alteration of Gills and Liver Histological Structure of Cyprinus carpio Exposed to Leachate - Tri Dewi Kusumaningrum Pribadi; Dzikrina Syahidah; Sairandri Dyah Harjanti; Desak Made Malini (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
One of the main problems in the waste management in Indonesia is the treatment of leachate, which mostly dumped to the river This research is aimed to obtain information of histological alteration in gills and liver of C. carpio L. exposed to leachate. Measurements on the water quality parameters comprised water temperature, pH, and dissolved oxygen (DO). This research was conducted by exposing leachate to C. carpio for 96 hours. The concentration of leachate were 0 ppm, 80 ppm, and 100 ppm. Histological preparation were made on the gills and liver using 10% fixative Neutral Buffered Formalin and Ehrlich Hematoxylin-Eosin staining with qualitative observation descriptive analyses for discussion. The result showed that increasing water temperature is directly proportional to the leachate concentration in the aquaria, while the value of pH and DO inversely proportional to the leachate concentration. Damages on the gills with 80 ppm leachate concentrasion were identified as follows: fusion of secondary gill filaments and hyperplasia of epithelial cell, along with karyorrhexis and hydropic degeneration on the liver. Damages on the gills of fishes exposed to leachate with 100 ppm concentrasion were identified as follows: fusion of secondary gill filaments, hyperplasia of epithelial cell, congestion, and edema along with karyorrhexis, hydropic degeneration and melanomacrophage centre (MMC) found on the liver. The results of this study can be used as an overview of the impact of an environmental pollution by leachate as indicated from histological damage to the gills and liver of C. carpio, thus contribute significan information to aquaculture sector and endorse better waste management